PENGARUH LKS BERBASIS PROJECT BASED LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA N 13 PADAN - Winda Sari; Murtiani Murtiani; Gusnedi Gusnedi (Universitas Negeri Padang, 2015)
The low physics learning outcomes of students in SMA N 13 Padang because students who have not mastered the concept. The cause is rarely student practicum and worksheets are used not lead students to think creatively and independently, so it need worksheets that can lead students to think creatively and independently. One type of worksheets that can be used to overcome these problems is worksheets based Project Based Learning. Therefore, this research was conducted to determine the effect of worksheets based Project Based Learning on learning outcomes physics class X SMA N 13 Padang on the competence of knowledge, attitudes, and skills. This research is a Quasi-Experimental Researc with design Randomized Control Only Group Design. The population in this research were all students in the tenth grade at SMA N 13 Padang enrolled in the academic year 2014/2015. Sampling was determined through purposive sampling technique. The instrument in this research is the ultimate test for competency knowledge, attitudes observation sheet for competence, and performance assessment sheets for competency skills. Data were analyzed by using test the equality of two average. The results shows that the competence of knowledge, the average value of the final test experimental class is 77.03 while the control class 66.09. On the attitude of competence, the average value of the experiment showed a very good grade while good control class. On competency skills, the average value of the experimental class is 85.56 while the control class 81.28. Therefore, the working hypothesis which states that